2021
DOI: 10.1371/journal.pntd.0009107
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal ultrasound in the diagnostic work-up of visceral leishmaniasis and for detection of complications of spleen aspiration

Abstract: Introduction Abdominal ultrasound (US) is increasingly used in the diagnostic work-up of infectious diseases, but studies on its diagnostic value in visceral leishmaniasis (VL) are lacking. US could help to identify complications of spleen aspiration (SA). We aimed to assess the diagnostic value of US and the evolution of findings after VL treatment; the incidence and degree of splenic injury; and the pain perceived during SA. Methodology/result We conducted a cross-sectional prospective study at the Leishma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The study from Morocco on POCUS screening for cystic echinococcosis (CE) 22 an infectious disease with a primarily imaging-based diagnosis, 86 proved not only feasible and successful in identifying the disease, but is a good example that POCUS can also support the implementation of disease control activities. POCUS for the detection of urogenital schistosomiasis, 49 POCUS to guide management of severe malaria, 87 POCUS for early detection of vascular leakage in severe dengue 88 and POCUS for visceral leishmaniasis 89,90 FAST: focused assessment with sonography for trauma, FASH: focused assessment with sonography for HIV-associated tuberculosis, FASE: focused assessment with sonography for echinococcosis.…”
Section: Discussionmentioning
confidence: 99%
“…The study from Morocco on POCUS screening for cystic echinococcosis (CE) 22 an infectious disease with a primarily imaging-based diagnosis, 86 proved not only feasible and successful in identifying the disease, but is a good example that POCUS can also support the implementation of disease control activities. POCUS for the detection of urogenital schistosomiasis, 49 POCUS to guide management of severe malaria, 87 POCUS for early detection of vascular leakage in severe dengue 88 and POCUS for visceral leishmaniasis 89,90 FAST: focused assessment with sonography for trauma, FASH: focused assessment with sonography for HIV-associated tuberculosis, FASE: focused assessment with sonography for echinococcosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to observations of lymphadenopathy, small hypoechoic lesions are often detected in the spleen [78,79,81,[94][95][96][97][98][99][100]. Focal liver lesions are extremely rare [101]. Bükte et al report a case of visceral leishmaniasis with such lesions [97].…”
Section: Leishmaniasismentioning
confidence: 99%
“…21 A study conducted in Ethiopia reported that there is no evidence to support the routine use of abdominal US in the management of VL except to detect subclinical complications of splenic aspiration. 29 However, previous studies have given limited attention to chest imaging findings, which are not uncommon, with a sparse attempt to review the diagnostic yield of specimens from the identified lesions. To the best of our knowledge, this is the first systematic review done on this subject.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Tissue sampling, especially splenic aspiration, can lead to serious complications in inexperienced hands. 20 , 28 , 29 Clinical findings in VL are nonspecific 12 , 16 and immunosuppressed patients, AIDS patients, transplant recipients, and children with primary immunodeficiency can have atypical presentations. 18 20 These all add to a complex diagnosis of VL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation